Quem faz política no Ceará? Uma análise da sub-representação das mulheres no legislativo cearense entre 1998 a 2022 - Bezerra, Bruna Ferreira de Araújo (2024)
This dissertation analyzes the underrepresentation of female State Deputies in Ceará between 1998 and 2022. The main objective of the research is to understand women's political representation in Ceará by investigating the sociodemographic profile of candidates for the position of State Deputy during this period. Additionally, the study aims to examine the contributions of feminism as a social movement and theoretical framework, as well as evaluate actions to promote women's participation in politics. To achieve this, a bibliographic review was conducted on feminist theories and political representation, followed by a qualitative and quantitative data collection and analysis using the "Estatísticas Eleitorais" and "Divulgacand" databases from the Brazilian Superior Electoral Court (TSE). The study outlines the sociodemographic profile of the candidates, analyzing gender, race, class, marital status, educational level, and age group. The results reveal that women's presence in the Ceará State Legislature has been limited to only forty-two elected women over twenty-six years. Furthermore, the few women elected share specific characteristics: they are predominantly white, older, married, cisgender, hold higher education degrees, and have a medium-high level of declared wealth. The research also identified a lack of detailed data on race and gender identity among candidates, reflecting the historical invisibility of Black, Indigenous, and transgender women. The main conclusions indicate that: (1) the creation and implementation of public policies must consider intersectionality, including the expansion of quota policies and the establishment of racial quotas; (2) stricter sanctions must be applied to prevent fraud in gender quotas, along with reinforcing efforts to combat gender-based political violence, particularly as Black and transgender women face this violence intertwined with racism and transphobia; (3) there is a need to improve data collection by institutions such as the Superior Electoral Court to enhance electoral transparency and support the formulation of public policies; (4) political power in Ceará remains predominantly held by a homogeneous group of white, cisgender men from economically and politically privileged backgrounds.